2010
DOI: 10.1152/ajpregu.00402.2010
|View full text |Cite
|
Sign up to set email alerts
|

The continuum of hybrid IIX/IIB fibers in normal mouse muscles: MHC isoform proportions and spatial distribution within single fibers

Abstract: Although skeletal muscle fiber types are often defined as belonging to discrete categories, many muscles possess fibers with intermediate phenotypes. These hybrid fiber types can be identified by their expression of two or more myosin heavy chain (MHC) isoforms within the same single fiber. In mouse muscles, the most common hybrid fibers are those coexpressing the IIX and IIB MHC isoforms. In the present study, we focused on these IIX/IIB fibers from normal mouse muscles to determine the relative proportions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 74 publications
2
36
0
Order By: Relevance
“…However, although the MyHC composition differed from one muscle part to another, they did not investigate whether the MyHC composition differed over the length of a single fiber. Other studies observed a variation in MyHC composition in parts of leg muscle fibers of adult [Zhang et al, 2010] and newly weaned mice [Brummer et al, 2013] also by means of gel electrophoresis. It might be expected that muscles, which are still growing, have newly fused myoblasts (from satellite cells) that express a different MyHC isoform.…”
Section: Introductionmentioning
confidence: 87%
“…However, although the MyHC composition differed from one muscle part to another, they did not investigate whether the MyHC composition differed over the length of a single fiber. Other studies observed a variation in MyHC composition in parts of leg muscle fibers of adult [Zhang et al, 2010] and newly weaned mice [Brummer et al, 2013] also by means of gel electrophoresis. It might be expected that muscles, which are still growing, have newly fused myoblasts (from satellite cells) that express a different MyHC isoform.…”
Section: Introductionmentioning
confidence: 87%
“…A total of 2,587 fibers were analyzed in this study (818 SOL,723 BR and 1,046 TA), with approximately 100 fibers sampled per animal. Each fiber was placed into a microcentrifuge tube containing ∼ 30 μl of sample buffer containing 8 M urea, 2 M thiourea, 50 m M Tris base, 75 m M dithiothreitol, 3% sodium dodecyl sulfate (SDS) and 0.004% bromophenol blue, pH 6.8 [Blough et al, 1996;Zhang et al, 2010]. Samples were heated to 65 ° C for 15 min and 10 μl of each sample was applied to the gel.…”
Section: Single Fiber Analysesmentioning
confidence: 99%
“…The presence of hundreds of individual nuclei, along with limitations in diffusional distance, means that the different myonuclear domains can contain distinct protein assemblages from one another [Pavlath et al, 1989;Newlands et al, 1998;Allen et al, 1999]. Indeed, a number of studies have demonstrated that myosin expression does vary along the length within certain single muscle fibers [Staron and Pette, 1987;Edman et al, 1988;Termin et al, 1989;Sakuma et al, 1995;Peuker and Pette, 1997;Lutz et al, 2001;Zhang et al, 2010]. While it is currently unknown how prevalent such asymmetries are in normal muscles, it is plausible that longitudinal differences in MHC content may reflect dy-namic changes in fiber type.…”
Section: Segmental Differences In Fiber Typementioning
confidence: 99%
See 2 more Smart Citations